A Model for Anocracy - Grigoryan, Aleksandr Hrachik (Journal of Income Distribution®, 2015)
In this article a dynasty model is developed with a non-benevolent planner who maximizes the welfare of a size-adjusted elite. Joining the elite is costly, as it provides access to financial intermediation for new entrants. Some of the incumbents collect payments, which are redistributed back based on their welfare status. Corrupt incumbents necessarily emerge and amplify negative externality towards the poor through collateral, which is required for loan market participation. The resulting model is useful to describe the evolution of incomplete democracies (anocracies). Elites alternate with each other, and successors discipline their predecessors with expropriation threats on collected rents should too many licenses for intermediation be sold, as that accelerates the wealth equalization process. This disciplinary mechanism, however, mitigates wealth differences, since it creates a burden on corruption, and the elite is expanded through intermediaries.